Images of the enemy: the SPD's perception of National Socialism in Augsburg, with particular reference to the portrayal of Nazism in the Schwabische Volkszeitung, 1928-1933 - Liddell, Eric (University of Edinburgh, 1996)
The thesis is a study of how the NSDAP was perceived and interpreted by the SPD in the south Bavarian city of Augsburg during the period 1928-1933. It particularly seeks to investigate the response of the Social Democratic rank and file to the rise of Nazism, and to explore the relationship between the local SPD's literary and propaganda output, and that response. Thus, the SPD's failure to defend itself from National Socialist attack in 1933 is examined from a hitherto neglected perspective: that is, by asking what image of the Nazi enemy Augsburg's Social Democrats possessed, to what extent that image was mediated by the SPD's 'official' analysis of the NSDAP, and what contribution the form of that image made to the SPD's fate. In the absence of wide-ranging archival sources which would allow the construction of a detailed portrait of the organisational structure and development of the SPD in Augsburg during the Weimar Republic, or the recovery of the patterns of day-to-day working-class life and politics, the thesis concentrates on the local Social Democratic newspaper, the Schwabische Volkszeitung. It analyses thoroughly the latter's material on National Socialism, and relates this to the general history of the SPD in the city in the era of the NSDAP's growth. The question is, further, addressed of how effective the SPD's propaganda reaction to Nazism, as reflected in the Schwabische Volkszeitung was in immunising its rank-and-file support against National Socialism, and in instilling within that support the desire and willingness to defend itself from the NSDAP's attacks. Chapter 1 outlines the political, social and economic structures, and historical preconditions, which provided the context within which the SPD's struggle with Nazism In Augsburg occurred. Chapters 2 to 10 deal with var10US aspects of the Schwabische Volkszeitungts engagement with National Socialism, and discuss their wider implications. The main finding of the thesis is that, in the case of the SPD in Augsburg, the party's capitulation in 1933 cannot be considered the result of a failure to warn its supporters about the threat posed by National Socialism; rather than the SPD's long-term structural inadequacies, which a close reading of the Schwabische Volkszeitung's approach to Nazism also illuminates, were far more crucial 1n determining its behaviour. Chapter 11 applies this finding to events in Augsburg after Hitler's appointment as Chancellor, and concludes that a desire for mass action in defence of the SPD did exist amongst the city's core Social Democrats, and had indeed been partially created by the success of the party's anti-Nazi propaganda, but that this desire was ultimately frustrated by the SPD's inherent and inescapable caution.
Keywords: History